2019
DOI: 10.1016/j.scib.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Discovering unusual structures from exception using big data and machine learning techniques

Abstract: a b s t r a c tRecently, machine learning (ML) has become a widely used technique in materials science study. Most work focuses on predicting the rule and overall trend by building a machine learning model. However, new insights are often learnt from exceptions against the overall trend. In this work, we demonstrate that how unusual structures are discovered from exceptions when machine learning is used to get the relationship between atomic and electronic structures based on big data from high-throughput calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Although it is crucial for understanding the properties of the solids, the structural units of them are usually inaccessible. In our previous work, we have applied machine learning to get the relationship between atomic and electronic structures and uncover unusual structural units from exceptions [38]. Our previous work on cathode material LiNi 0.5 Mn 0.5 O 2 has revealed that the d-p-d Möbius aromaticity within the fragmented Mn 6 -ring units contribute to stability and the interlayer ordering of the material [39].…”
Section: Resultsmentioning
confidence: 99%
“…Although it is crucial for understanding the properties of the solids, the structural units of them are usually inaccessible. In our previous work, we have applied machine learning to get the relationship between atomic and electronic structures and uncover unusual structural units from exceptions [38]. Our previous work on cathode material LiNi 0.5 Mn 0.5 O 2 has revealed that the d-p-d Möbius aromaticity within the fragmented Mn 6 -ring units contribute to stability and the interlayer ordering of the material [39].…”
Section: Resultsmentioning
confidence: 99%
“…Those inaccurate prediction results should not ascribe to algorithms but the lack of training data. Notably, Pan et al [3] developed a material structure database and studied the bandgap of material structure by ML method. Thirdly, developing the technical databases for characterizing energy materials is important.…”
Section: Discussionmentioning
confidence: 99%
“…Energy materials are materials used in energy harvesting, storage and conversion filed such as photovoltaics, batteries, fuel cells and photo(electro)catalysis, etc. Energy materials including intermetallic alloys, metal/covalent-or-ganic frameworks, carbon materials, perovskite and spinel materials play an important role in global economic development [1][2][3][4][5]. For instance, as an efficient ammonia synthesis materials, iron (Fe)-based catalysts invented in the early 20th century have promoted food production, which feeds billions of people [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the boiling experiments in these studies are conducted on one-dimensional (1D) wires, which cannot represent the complex and volatile bubble motions associated with realistic two-dimensional (2D) or three-dimensional (3D) surfaces. Unfortunately, the results from many past models were hard to physically comprehend as they relied on abstract input features such as groups of pixels or principal components 51 . In addition to this, there have been no such an effort to practice machine learning based computer vision link bubble dynamics and boiling processes.…”
Section: Introductionmentioning
confidence: 99%